Improving the set of documents used in accounting between a bank and an enterprise - Tilov Jamshid Norbabo oglu (THE INNOVATION ECONOMY, 2026)
This article examines the issues of improving the set of documents used in settlements between banks and enterprises. The study analyzes the role of accounting documents in ensuring the accuracy, transparency, and reliability of financial transactions. Using the document analysis method, the current state of bank statements, payment orders, contracts, and accounting registers was assessed, and key problems in their application were identified. The findings indicate that document standardization, increased use of electronic documentation, and improved reconciliation processes between banks and enterprises contribute to enhancing the efficiency and reliability of financial settlements